Weathered coal loaded zero-valent iron composite material as well as preparation method and application thereof
By combining the weathered coal-loaded zero-valent iron composite material and permonosulfate, the problem of attenuation of adsorption catalytic performance caused by the agglomeration of zero-valent iron is solved, and the effect of efficient removal of polycyclic aromatic hydrocarbons in water and soil is achieved, and good circulation performance and soil improvement effects are demonstrated.
Patent Information
- Application Number
- CN202510091559.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The prior art has problems such as low efficiency, high cost and poor stability when removing polycyclic aromatic hydrocarbons (PAHs) pollution in water and soil, especially the prone to agglomeration of zero-valent iron (ZVI) leads to attenuation of adsorption catalytic performance.
Weathered coal-loaded zero-valent iron composite material (CM@ZVI) is used to synthesize zero-valent iron particles in situ by carbon thermal reduction method, and combine with permonosulphate (PMS) to form activated permonosulphate adsorption and degradation materials for removing PAHs in water and soil.
The specific surface area and adsorption and degradation properties of zero-valent iron are improved, and the removal rate of PAHs is significantly improved. Especially in water, the removal rate of naphthalene reaches 97.3%, and the removal rate in soil also reaches 86.2%~92.2%, and the material has good circulation performance and soil improvement effect.
Smart Images

Figure CN119657144A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water / soil treatment, and in particular relates to a weathered coal-loaded zero-valent iron composite material and a preparation method and application thereof. Background Art
[0002] Due to the acceleration of industrialization, the increase of waste emissions and the impact of human activities such as fuel combustion, polycyclic aromatic hydrocarbons (PAHs) have been widely present and spread in environmental media. To date, there are more than 100 known PAHs compounds. The vast majority of PAHs have "triple effects" such as carcinogenicity, teratogenicity and mutagenicity. As typical persistent organic pollutants, they are constantly circulating in the atmosphere, water bodies, soil and biosphere and are difficult to be completely mineralized. The hydrophobicity and lipophilicity of PAHs make them easily adsorbed on the surface of water sediments or soil colloids. At the same time, PAHs in water bodies and soil can also enter the ecosystem through the food chain, ultimately threatening human health. Therefore, there is an urgent need to develop economical and efficient new technologies or new materials to achieve the complete mineralization and removal of PAHs, thereby reducing their negative impact on the environment and health.
[0003] At present, the common methods for treating PAHs mainly include physical methods, biological methods, and chemical methods. Although the above treatment methods can all be applied to the treatment of PAHs pollution, they each have their own advantages and disadvantages. The physical remediation method only causes a phase transfer, and does not completely remove the pollutants, and the removal effect is limited by the solubility of the pollutants themselves and the properties of the adsorbent. The biological remediation method is an environmentally friendly, low-cost, and relatively low-tech remediation technology, but the degradation effect is affected by environmental factors such as the type of microbial community and the chemical properties of PAHs, and the degradation rate of organic pollutants is slow; in addition, when the concentration of PAHs is high, biological activity is limited, which has a greater impact on degradation and has certain limitations. The chemical remediation method has a fast effect, a short remediation cycle, and strong environmental adaptability, especially for site contaminated soil or environmental media with severe PAHs pollution. Among them, the advanced oxidation method based on persulfate in the chemical remediation method has been widely concerned and applied because of its simple operation, strong environmental adaptability, and high efficiency in oxidative degradation of high-concentration PAHs pollutants, and basically no secondary pollution after the reaction. Among the many persulfate activators, zero-valent iron (ZVI) has attracted widespread attention due to its non-toxicity, environmental friendliness, and lower cost and availability than other transition metal ions. However, ZVI is prone to agglomeration in water, resulting in a reduction in specific surface area and insufficient exposure of active sites, which leads to a decrease in its adsorption catalytic performance. It is generally necessary to screen efficient, cheap and readily available materials as carriers to prevent the agglomeration of ZVI. At present, although there have been reports on the use of carbon-based materials, metal compounds or biomaterials as carriers for loading ZVI, there are still problems such as relatively poor stability, unsatisfactory dispersibility and regeneration, and high cost of carrier materials. Therefore, it is of great significance to develop a green, efficient and low-cost persulfate activator for removing or reducing the pollution of polycyclic aromatic hydrocarbons in water / soil. Summary of the invention
[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing a persulfate activator which is simple, easy to prepare, green, efficient and low-cost in view of the shortcomings of the prior art. The material is used to activate persulfate to remove PAHs in water / soil, which is of great significance in the treatment of PAHs-contaminated water / soil.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a weathered coal-loaded zero-valent iron composite material comprises the following steps: (1) Grind the weathered coal, remove impurities, and store it in a brown storage bottle and seal it; (2) adding the weathered coal obtained in step (1) to a potassium ferrate (K2FeO4) aqueous solution, stirring and mixing at room temperature, drying and grinding, and then calcining at high temperature in an inert atmosphere to perform a carbon thermal reduction reaction. During the high-temperature carbonization and decomposition process, humus and other organic matter in the weathered coal generates some reducing gases, and the potassium ferrate is reduced by the reducing gases to generate zero-valent iron in situ; (3) The calcined product in step (2) is cooled to room temperature and washed with pure water until neutral, and finally dried in vacuum to obtain CM@ZVI, which is sealed and stored to prevent oxidation, thereby preparing a weathered coal-loaded zero-valent iron-activated monosulfate adsorption degradation material.
[0006] Specifically, in step (1), the weathered coal is a natural organic-inorganic complex, the organic component of which is mainly humic acid with a mass fraction greater than 30%, and the inorganic component in the weathered coal contains aluminosilicates; the inorganic component in the weathered coal also contains a small amount of metal compounds, and the metal compounds are metal compounds such as iron, magnesium or calcium.
[0007] Specifically, in step (1), the weathered coal is first dried at 60-80°C (preferably 80°C) for 6-12h (preferably 8h), ground through a 100-200 mesh (preferably 200 mesh) sieve, washed with water and filtered to remove water-soluble impurities, then dried and ground again to obtain weathered coal fine powder with an average particle size of no more than 30 microns.
[0008] Specifically, in step (2), the mass concentration of potassium ferrate in the potassium ferrate aqueous solution is 0.1-1 g / 50 ml, preferably 0.5 g / 50 ml; the mass ratio of the weathered coal to potassium ferrate is (10:1)-(1:1), preferably 2:1.
[0009] Specifically, in step (2), the stirring and mixing is performed by magnetic stirring to achieve uniform mixing, the stirring speed is 500-600 r / min, preferably 550 r / min, and the stirring time is 10-12 h, preferably 12 h; the drying is performed at 60-80 °C for 12-24 h, and the grinding is performed by grinding into fine particles using an agate mortar.
[0010] Specifically, in step (2), the high temperature calcination is carried out under the following conditions: heating to 600-900°C at a heating rate of 5-10°C / min, and then calcining for 1-3h, preferably calcining at 800°C for 2h, and the inert atmosphere is N2 atmosphere.
[0011] Specifically, in step (3), the neutral pH is 7-7.5, and the vacuum drying is carried out at 60°C-80°C for 12h-24h, followed by sealing and airtight storage.
[0012] Furthermore, the weathered coal-loaded zero-valent iron composite material prepared by the above-mentioned preparation method is also within the protection scope of the present invention.
[0013] Furthermore, the present invention also claims to protect the use of the above-mentioned weathered coal-loaded zero-valent iron composite material in activating permonosulfate to adsorb and degrade polycyclic aromatic hydrocarbons in water or soil.
[0014] Specifically, the polycyclic aromatic hydrocarbons are at least one of naphthalene (NAP), phenanthrene (PHE) and pyrene (PYR).
[0015] The specific method is to add a certain amount of CM@ZVI and permonosulfate (PMS) to water / soil containing a certain concentration of PAHs, and remove PAHs through adsorption and degradation reaction.
[0016] The weathered coal-loaded zero-valent iron activated permonosulfate adsorption and degradation material of the present invention has a removal rate of up to 97.3% for NAP in artificially polluted water. The weathered coal-loaded zero-valent iron activated permonosulfate adsorption and degradation material has removal rates of 86.2%, 87.3% and 92.2% for NAP (41.83 mg / kg), PHE (10.08 mg / kg) and PYR (11.17 mg / kg) in artificially polluted soil, respectively. The weathered coal-loaded zero-valent iron activated permonosulfate adsorption and degradation material has a certain remediation effect on polycyclic aromatic hydrocarbons in actual polluted soil, and the removal rates of pyrene PYR (116 mg / kg), phenanthrene PHE (44.2 mg / kg), anthracene ANT (11.9 mg / kg) and fluoranthene FLT (98.6 mg / kg) are 53.9%, 73.2%, 55.3% and 58.7%, respectively.
[0017] Weathered coal is a natural metamorphic product of coal, mainly composed of organic matter such as humus and inorganic minerals. Among them, organic matter includes humic acid and residual coal (humus); inorganic matter (ash) mainly includes aluminosilicates, carbonates (kaolinite, quartz) and a small amount of iron, magnesium, zinc, manganese and other compounds. Because the humic acid structure itself contains rich oxygen-containing functional groups such as carboxyl, hydroxyl, and quinone, it has high adsorption / reaction activity, and mineral source humic acid is extracted and separated from weathered coal, so the humic acid substances in weathered coal also have the functions of adsorption, complexation, exchange and transfer of electrons to promote oxidative degradation. Previous studies have shown that ZVI effectively removes a variety of pollutants through mechanisms such as adsorption, precipitation, oxidation, reduction, and surface complexation. However, if ZVI is used alone, there are obvious disadvantages, such as small size, strong magnetism, high surface energy and easy oxidation. It is very easy to condense into a chain structure in water or soil solution and agglomerate, resulting in a reduction in specific surface area and insufficient exposure of active sites. Weathered coal is an organic-inorganic complex naturally formed in nature. It has high reactivity and multifunctionality due to its stable structure and rich surface functional groups. When used as a carrier, it can not only achieve uniform loading of nano zero-valent iron, but also further improve the adsorption and activation degradation performance through the synergistic effect between them. In addition, the humus and metal elements such as potassium, calcium, and magnesium contained in weathered coal are also essential nutrients for plant growth. According to the research results of the inventors, during the addition of ZVI precursor K2FeO4 and high-temperature annealing, the reducing gas generated during the carbonization of organic substances such as humus in weathered coal can reduce K2FeO4 to ZVI and load it evenly on the modified weathered coal in situ; at the same time, substances such as KOH generated by the decomposition of K2FeO4 can chemically activate weathered coal and significantly increase the specific surface area of the composite material. In short, weathered coal is used as a carrier to activate and load zero-valent iron in situ through annealing to activate persulfate to remove PAHs in water / soil, achieving low-cost and high-efficiency adsorption and degradation of PAHs in water / soil.
[0018] Weathered coal (CM) used in the present invention is a naturally formed composite material, mainly composed of natural organic polymers such as humus and inorganic minerals, and the organic part contains rich oxygen-containing functional groups. In environmental remediation applications, weathered coal removes PHAs pollutants in the environment through mineralization degradation by adsorption, complexation, or redox. Iron is the fourth most abundant element in the earth's crust. Zero-valent iron (ZVI) is widely used as a catalyst for AOPs degradation of organic pollutants through adsorption, precipitation, redox, surface complexation and other mechanisms due to its non-toxicity, abundant reserves, low price and easy preparation, and is considered to be a promising material. Weathered coal, as a natural organic-inorganic complex, has a stable structure and rich surface functional groups. After high-temperature annealing with K2FeO4, it can not only generate zero-valent iron in situ and achieve uniform loading, but also further improve the adsorption and activation degradation performance through the synergistic effect between them. In addition, ZVI materials are magnetically separable and have significant economic and environmental benefits.
[0019] The weathered coal-loaded zero-valent iron material CM@ZVI was synthesized in situ by a simple carbothermal reduction method, which can solve the problem of easy agglomeration of zero-valent iron, increase the specific surface area of the material, improve the adsorption and degradation properties, and accelerate the reaction process and efficiency. Beneficial Effects
[0020] (1) The present invention adopts a simple carbothermal reduction method to synthesize CM@ZVI. The surface of the material is loaded with zero-valent iron particles of different sizes, which increases the specific surface area of the composite material and exposes the active sites of the material. These characteristics provide more adsorption sites and effectively prevent the agglomeration of zero-valent iron during the synthesis process. At the same time, it can effectively shorten the contact distance between the pollutant and the activator / oxidant, thereby accelerating the reaction process.
[0021] (2) The removal rates of CM@ZVI prepared by the present invention for naphthalene in water and naphthalene, phenanthrene and pyrene in soil can reach 97.3%, 86.2%, 87.3% and 92.2%, respectively, which indicates that CM@ZVI can efficiently activate PMS to remove PAHs in water / soil. CM@ZVI can be recycled when used in water, or restored by annealing. When CM@ZVI is used for naphthalene contamination in soil, it also has certain beneficial effects on soil improvement. This indicates that CM@ZVI has certain application prospects for the remediation of PAHs in soil. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0023] Figure 1This is a graph showing the removal performance of NAP in water at different temperature ratios of CM@ZVI in Example 1.
[0024] Figure 2 This is a graph showing the removal performance of NAP in water by different iron precursors in Example 2.
[0025] Figure 3 The SEM and TEM images of CM and CM@ZVI materials in Example 3 are shown in FIG. Figure 3 a is weathered coal raw material, Figure 3 b is CM@ZVI, Figure 3 c is the Mapping diagram of CM@ZVI, Figure 3 df is the TEM image of CM@ZVI.
[0026] Figure 4 Nitrogen adsorption-desorption isotherm diagram of CM@ZVI.
[0027] Figure 5 This is the XRD pattern of CM@ZVI.
[0028] Figure 6 FTIR graph of CM@ZVI.
[0029] Figure 7 This is the XPS pattern of CM@ZVI.
[0030] Figure 8 Figure 2 shows CM@ZVI and its removal performance for NAP in water.
[0031] Fig. 9 The cycling performance diagram of CM@ZVI.
[0032] Fig.10 This is the removal performance diagram of CM@ZVI for NAP, PHE, and BYR in soil.
[0033] Fig.11 This is the removal performance diagram of CM@ZVI for several typical PAHs in actual contaminated soil. DETAILED DESCRIPTION
[0034] The present invention can be better understood with reference to the following examples.
[0035] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0036] The weathered coal used in the embodiment of the present invention comes from Jiaokou County, Luliang City, Shanxi Province, with a pH of 6.2. After drying, the mass fraction of humic acid, an organic component, is about 45%, aluminum oxide is about 9.3%, silicon dioxide is 33.0%, and calcium oxide / potassium and iron are about 12%.
[0037] Potassium ferrate was purchased from Aladdin Biochemical Technology Co., Ltd.
[0038] In the embodiment of the present invention, the removal of PAHs by the measuring material is determined by high performance liquid chromatography to determine the concentration of PAHs, the removal rate of NAP in water is calculated according to formula 1, the removal rate of NAP in soil is calculated according to formula 2, and the removal rate of PHE and PYR in soil is calculated according to formula 3.
[0039] (Formula 1); (Formula 2); In formula 1: is the removal rate (%); C0、C i represent the initial concentration and the concentration of NAP in the solution at the time of sampling (mg·L -1 ).
[0040] In formula 2: is the removal rate (%); C0 is the concentration of NAP in blank soil (mg / kg); C is the concentration of residual NAP in the soil measured after the reaction (mg / kg); m is the mass of soil used in the experiment (kg); C w is the concentration of NAP dissolved in the supernatant (mg / kg); V w is the volume of the supernatant (L).
[0041] (Formula 3); is the removal rate (%); C0、C z Represent the initial and final concentrations of PHE and PYR in soil (mg / kg), respectively. Example 1
[0042] Screening of permonosulfate adsorption and degradation materials activated by weathered coal loaded with zero-valent iron.
[0043] Preparation of weathered coal-loaded zero-valent iron material: Weathered coal (CM) was dried, ground, sieved with 200 mesh, washed, filtered, and dried for later use. 1 g of weathered coal was weighed and added to 50 ml of solution containing 0.01 g, 0.5 g, and 1 g of K2FeO4, respectively. After magnetic stirring at room temperature for 12 h, it was dried and ground at 80 °C, and calcined at 600 °C, 700 °C, 800 °C, and 900 °C (heating rate of 5 °C / min) for 2 h (N 2 atmosphere), cooled to room temperature, washed with pure water until neutral, and then placed in a vacuum and dried at 60°C for 12 h to obtain materials with different temperatures and proportions, which were respectively abbreviated as 600-CZ10, 600-CZ2, 600-CZ1, 700-CZ10, 700-CZ2, 700-CZ1, 800-CZ10, 800-CZ2, 800-CZ1, 900-CZ10, 900-CZ2, and 900-CZ1.
[0044] Removal of NAP from water using materials at different temperatures and ratios: First, prepare a 1g / L naphthalene stock solution, dilute the naphthalene stock solution into a 10 mg / L simulated NAP contamination solution (dissolve with 20% acetonitrile, shake well before use). Weigh 20 mg of materials and 20 mg of PMS at different temperature ratios in a conical flask, then measure 100 mL of NAP solution and add it to the conical flask, shake evenly, shake on a shaker at 180 r / min for 120 min at room temperature 25 °C, then take a 1ml sample and place it in a 5 mL syringe, and filter it with a 0.22 μm organic pinhole filter. Take 0.5 mL of the filtered solution and add it to a liquid phase vial containing 0.5 mL of methanol, and perform high-performance liquid chromatography to detect the residual concentration.
[0045] Depend on Figure 1 It can be seen that the 800-CZ2 material has the highest NAP removal rate of 91.9%. Therefore, the preferred calcination temperature is 800°C, and the preferred ratio is weathered coal: potassium ferrate = 2:1. The subsequent materials used are all at this temperature and ratio and are recorded as CM@ZVI. Example 2
[0046] Screening of different iron precursor materials.
[0047] Preparation of different iron precursor materials: Weigh 1g of weathered coal and add it into 50ml solutions of FeCl3•6H2O, FeSO4•7H2O, and K2FeO4 containing the same iron content. After magnetic stirring at room temperature for 12h, dry and grind at 80℃, calcine at 800℃ (heating rate of 5℃ / min) for 2h (under N2 atmosphere), cool to room temperature, wash with pure water until neutral, and then bake in a vacuum at 60℃ for 12h to obtain different iron precursor materials.
[0048] Removal of NAP from water by different iron precursor materials: Take 10mg / L simulated NAP contaminated solution, weigh 40mg of different iron precursor materials and 30mg of PMS in a conical flask, and then measure 100mL of NAP solution and add it to the above conical flask, shake evenly, shake on a shaker at 180r / min at room temperature 25℃ for 120min, take 1ml of sample at 5, 10, 30, 60, 90, 120min, put it in a 5mL syringe, and filter it with a 0.22μm organic pinhole filter. Take 0.5mL of the filtered solution and add it to a liquid phase vial containing 0.5mL of methanol, and perform high performance liquid chromatography to detect the residual concentration.
[0049] Depend on Figure 2 It can be seen that the material with K2FeO4 as the precursor has the best removal effect on NAP, with the highest being 99.2%. The common FeCl3•6H2O and FeSO4•7H2O as precursors cannot achieve the effect of K2FeO4, which are 74% and 48.8% respectively. This shows that the better effect of K2FeO4 as the precursor is because the synergistic effect between K2FeO4 and weathered coal is not achieved by the other two. Example 3
[0050] Preparation of weathered coal loaded zero-valent iron activated permonosulfate adsorption degradation material.
[0051] Preparation of weathered coal-loaded zero-valent iron material: The weathered coal (CM) was dried, ground, sieved through 200 mesh, washed, filtered, and dried for later use. 1 g of weathered coal was weighed and added to 50 ml of a solution containing 0.5 g of K2FeO4. After magnetic stirring at room temperature for 12 h, it was dried and ground at 80 °C. It was calcined at 800 °C (heating rate of 5 °C / min) for 2 h (under N2 atmosphere). After cooling to room temperature, it was washed with pure water until neutral and then dried in a vacuum at 60 °C for 12 h to obtain CM@ZVI.
[0052] Table 1 gives the elemental analysis results of weathered coal (CM) and CM@ZVI.
[0053] Table 1 ; Figure 3 The SEM images of CM and CM@ZVI and the TEM image of CM@ZVI. Figure 3 (a) The weathered coal is in irregular blocks with a relatively smooth surface and few pores; Figure 3 (b) shows that there are obvious small particles on the surface of weathered coal, and the distribution is relatively dispersed. Figure 3 (c) The element distribution of CM@ZVI mapping can confirm that this particle is zero-valent iron and has some pores on its surface. Figure 3(di) is the TEM image of CM@ZVI. It can be seen from the figure that zero-valent iron particles of different sizes and shapes are distributed on the surface and inside of the material, which is consistent with the SEM. There are lattice fringes with a spacing of 0.2016nm, corresponding to Fe 0 This indicates that zero-valent iron particles were formed on the surface and inside of the weathered coal during the reaction.
[0054] Figure 4 The nitrogen adsorption-desorption isotherm of CM@ZVI shows that there is an obvious hysteresis loop at medium and high relative pressures of 0.4~1.0 p / p0, which belongs to the IV type isotherm, corresponding to mesoporous materials. The specific surface area, total pore volume, pore size distribution and other information of the samples are shown in Table 2. As can be seen from the table, the specific surface area of CM@ZVI is much larger than that of CM (7.1633 m 2 / g, 324.79m 2 / g, the main reason is that KOH introduced by K2FeO4 plays a role in partial pore formation, and Fe 0 , the total pore volume ranges from 0.0345cm 3 / g increased to 0.0621cm 3 / g, the average pore size decreased from 16.28nm to 2.7495nm, which is consistent with the Fe 0 The structural phenomenon is consistent.
[0055] Table 2 Comparison of BET parameters of materials ; Figure 5 The XRD pattern of CM@ZVI shows that the sharp diffraction peaks of CM@ZVI at 2θ = 44.6 nm, 65.0 nm and 82.3 nm are respectively related to Fe 0 The (100), (200) and (211) faces of the weathered coal are well matched (JCPDS06-0696), indicating that α-Fe was successfully formed on the weathered coal. 0 . The crystallinity of SiO2 is the best in weathered coal. Simply calcining at 800°C does not change the crystal form of weathered coal, which is basically consistent with the crystal form of CM. The main component is SiO2, which mainly corresponds to the (100), (101) and (112) crystal planes of SiO2, corresponding to the standard card JCPDS46-1045. After the weathered coal reacts with K2FeO4, the characteristic peak intensity of SiO2 weakens, which is mainly attributed to the introduction of new substances, which will cause a series of reactions and phase transformation caused by the heat treatment process, transforming the crystalline SiO2 into an amorphous state.
[0056] Figure 6 This is the Fourier infrared spectrum of CM@ZVI. The 3406cm -1and CM@ZVI’s 3423cm -1 There is a broad peak related to the -OH group nearby, which corresponds to the stretching vibration of water molecules, indicating the presence of hydroxyl groups on the surface of the material. 1800~1500cm -1 represents C=O (carboxyl, ester, ketone, etc.), which exists at 1578 cm in the spectra of CM and CM@ZVI. -1 and 1634 cm -1 , are stretching vibrations of aromatic rings. CM at 1387cm -1 There is a characteristic peak at 1113~896 cm, which is attributed to the CO absorption peak. -1 is the asymmetric stretching vibration of Si-OT (T represents Al or Si), and this characteristic peak exists in the spectra of CM and CM@ZVI within this range. -1 A new broad peak appears at , which may correspond to the characteristic peak of Fe-O stretching vibration, indicating that the reaction of K2FeO4 with CM forms new functional groups on its surface. At the same time, many characteristic peaks of CM weaken, which indicates that the structure of CM is destroyed during the reaction with K2FeO4.
[0057] Figure 7 This is the XPS graph of CM@ZVI. The C and O contents are relatively high on the surface of the material, while the Fe content is relatively low. It is possible that some Fe has entered the interior of the material. Figure 7 (b) is C1s. The C at 284.8 eV, 285.68 eV, and 289.32 eV come from the C atoms in CC, CO, and C=O, respectively. Due to the complex components of weathered coal, the metal carbonates contained therein have certain residues in the entire material preparation process. The C at 293.72 eV may come from the C atoms in the metal carbonates. Figure 7 (c) is the O1s fine spectrum, with 530.65 eV, 531.34 eV, and 532.48 eV corresponding to Fe-O, C=O, and CO, respectively. During the preparation and storage of the material, it is inevitable that the zero-valent iron on the surface of the material will be oxidized and combine with O to form Fe-O. Figure 7 (d) is the fine spectrum of Fe2p, where 707.18 eV, 711.09 eV, 714.77 eV, and 724.69 eV correspond to Fe 0 , Fe 2+ , Fe 3+ , Fe 2+ . Example 4
[0058] Removal of naphthalene (NAP) from water bodies.
[0059] (1) Removal of NAP from water by CM@ZVI: Weigh 40 mg of CM@ZVI composite material and 40 mg of PMS in a conical flask, and then weigh 100 mL of NAP solution and add it to the conical flask. Oscillate evenly, and oscillate on a shaker at 180 r / min for 120 min at room temperature (25 °C). Take 1 ml of sample at 2, 5, 10, 30, 60, 90, and 120 min, put it into a 5 mL syringe, and filter it with a 0.22 μm organic pinhole filter. Take 0.5 mL of the filtered solution and add it to a liquid phase vial containing 0.5 mL of methanol, and perform high performance liquid chromatography to detect the residual concentration.
[0060] Depend on Figure 8 The CM@ZVI+PMS system has the best removal effect on NAP, up to 97.3%. CM@ZVI also has a good removal effect on NAP. This is because the zero-valent iron on the surface of the CM@ZVI material is oxidized to Fe 2+ , transfers two electrons to O2 to produce H2O2, while Fe 2+ It can react with the generated hydroxyl radicals and with the dissolved oxygen in the environment to generate superoxide radicals, which have a certain oxidative effect on NAP. Superoxide radicals can react with H + The reaction further generates 1 O2, after adding PMS, the removal effect and rate of NAP were significantly improved, which shows that CM@ZVI as an activated persulfate material has a good removal effect on NAP in water.
[0061] (2) Cyclic performance of CM@ZVI: The specific degradation experimental steps were the same as above, with a PMS concentration of 300 mg / L and a catalyst concentration of 400 mg / L. After each degradation experiment, the material was recovered with a magnet, washed with pure water several times until neutral, and then vacuum dried at 60 °C for 12 h for the next use. After repeating the above steps twice, the material after the second cycle was dried and placed in a tubular furnace at 800 °C for 2 h for annealing and then subjected to another degradation experiment.
[0062] like Fig. 9 As shown in the figure, when used for the first time, the removal rate of NAP reached up to 97.9%. However, when the material was collected, washed with water, dried and reused, the removal rate of NAP was only 63.47%. The effect of the material was greatly reduced when it was used for the second time. However, after the material was recycled and annealed at 800℃, the removal rate of NAP was restored and even better, reaching 100%. The effect of the material was reduced by 34.43% when used for the second time, and the stability performance was not good. The reason is (1) Fe 0 It is easy to oxidize. The oxidized material will weaken the effect of activating PMS, and after the reaction, Fe0 (2) The products or pollutants generated after the reaction will be adsorbed onto the surface or pores of the material, blocking the active sites and making it difficult for them to function. However, this shortcoming can be solved by re-annealing. The effect after re-annealing is as good as or even better than the first preparation, which shows that the material still has certain application advantages. Example 5
[0063] Removal of naphthalene (NAP), phenanthrene (PHE) and pyrene (PYR) in soil.
[0064] (1) CM@ZVI removes NAP, PHE, and PYR from soil: First, the soil is naturally air-dried, and the air-dried soil is ground after impurities are picked out, and passed through an 80-mesh sieve. A certain amount of ground and sieved soil is poured into a 1000 ml beaker, and a certain amount of naphthalene / phenanthrene / pyrene is weighed and dissolved in acetone (naphthalene is contaminated alone, and phenanthrene and pyrene are contaminated together). The prepared contaminated solution is poured into the beaker, and the mixture is stirred thoroughly with a glass rod to mix evenly. Then, the mixture is placed in a fume hood for 7 days to allow the acetone to evaporate, and matured for 1 to 2 weeks. The prepared contaminated soil is refrigerated in a refrigerator at 4°C for later use. CM@ZVI is used in soil. 2 g of soil is placed in a 50 ml brown bottle, and a certain amount of PMS solution and CM@ZVI are added in sequence. The mixture is placed in a light-proof shaker at 25°C and 180 r / min for 24 h. After extraction, the content of the remaining PAHs is determined by high performance liquid chromatography, and the blank of each time is taken as the initial concentration of PAHs in the soil.
[0065] like Fig.10 Comparison of the removal rates of different pollutants by CM@ZVI / PMS. The removal of NAP (41.83 mg / kg) by adding 2.5wt% PMS and 2.5wt% CM@ZVI was 83.6%. The removal of PHE (10.08 mg / kg) by adding 1wt% PMS and 4wt% CM@ZVI was 87.3%. The removal of PYR (11.17 mg / kg) by adding 1wt% PMS and 4wt% CM@ZVI was 92.2%. This shows that CM@ZVI also has a certain removal potential for PAHs in soil.
[0066] (2) Determination of physical and chemical properties of NAP-contaminated soil before and after remediation: ① Soil pH: refer to GB7859-87, weigh 10g of soil to be tested in a conical flask, add 25ml of deionized water (maintaining a water-soil ratio of 2.5:1), shake and let stand for half an hour, and measure using a pH meter. Each group should have at least three parallels. ② Soil available potassium: refer to NYT889-2004, weigh 5g of soil, measure 50ml of 1mol / L neutral ammonium acetate extract, and measure using a flame atomic spectrophotometer. ③ Soil available phosphorus: refer to HJ704-2014, weigh 2.5g of soil, use 50ml of 0.5mol / L sodium bicarbonate solution for extraction, add a colorimetric reagent for color development, and measure the absorbance using a spectrophotometer. ④ Soil CEC: Weigh 3.5g soil, use 50ml 1.66cmol / L hexaamminecobalt trichloride extract, and then use a spectrophotometer to measure the absorbance. ⑤ Soil conductivity: Use the soil conductivity measurement electrode method (HJ802-2016) to measure. Take air-dried soil samples and add water in a ratio of 1:5, extract by shaking at 20℃, and measure the conductivity of the extract at 25℃. ⑥ Soil organic carbon: Weigh 3g air-dried soil samples, add 10ml 10% dilute hydrochloric acid, shake for 1h, centrifuge, pour off the supernatant, dry at 55℃ for 24h, pass through a 0.15mm sieve, weigh about 12mg, wrap the sample in tin foil, and measure it with an EA3000 elemental analyzer.
[0067] Table 3 Physical and chemical properties of soil before and after restoration ; As shown in Table 3, the soil physical and chemical properties changed significantly before and after remediation. The soil pH was buffered after remediation, which may be due to the consumption of some OH in the reaction process. - The generated iron ions can react with OH - Combined to form iron polymers; soil cation exchange capacity (CEC) refers to the total amount of various cations that soil colloids can absorb. This indicator is an important parameter to measure the soil's ability to retain fertilizer. Generally speaking, the higher the soil's CEC value, the stronger its ability to retain fertilizer. The normal range of CEC is 10-20 cmol + / kg, there are certain differences in different regions. The CEC before and after restoration is a little higher than the normal range; soil organic carbon is an important indicator to characterize changes in soil fertility, and it is the basis for high and stable crop yields and sustainable agricultural development. The soil organic carbon increased significantly before and after restoration, because some carbon substances in the materials entered the soil; soil conductivity can timely and effectively grasp the salt concentration, moisture status and other properties of the soil. The normal soil conductivity range is between 1-4mS / cm. Within this range, plants can usually grow normally. Too low conductivity may prevent plants from obtaining enough nutrients, while too high conductivity may damage the plant roots and affect their ability to absorb water and nutrients. The conductivity before the repair was too low, but after the repair, the conductivity can be increased to a normal level; Available potassium refers to the potassium in the soil that is easily absorbed and utilized by crops, reflecting the immediate potassium supply level of the soil to plants. The content of available potassium in the soil is generally 30~160mg / kg. The available potassium is high before and after the repair, which means that there is no need to apply additional potassium fertilizer. The increase in the content of available potassium after the repair is because the residual K element in the material preparation process enters the soil. PMS also contains K elements, which may enter the soil; Soil available phosphorus is the phosphorus component in the soil that can be absorbed by plants. The normal range of soil available phosphorus content is usually 10-20mg / kg. Within this range, the soil can provide enough phosphorus for plant absorption without causing excessive accumulation of phosphorus. After the repair, the content of available phosphorus has increased to a certain extent and reached the normal level.
[0068] Through the changes in the above physical and chemical properties, it is shown that using CM@ZVI materials to repair pollutants in the soil can not only remove pollutants in the soil but also play a certain role in improving the soil and enhancing soil fertility. CM@ZVI provides a new idea for soil remediation. Example 6
[0069] Removal of PAHs from actual contaminated soil.
[0070] Compared with simulated soil, the remediation effect of CM@ZVI on various PAHs in actual contaminated soil needs to be further investigated. To this end, soil samples were collected from a discontinued coking plant in Shaanxi Province, China, and CM@ZVI / PMS was used to remediate PAHs in the collected soil. Fig.11As shown in the figure, under the conditions of 4% CM@ZVI dosage and 3.5% PMS dosage, it has a certain remediation effect on PAHs in actual contaminated soil. Among them, the removal rate of pyrene PYR (initial concentration of pollutant 116 mg / kg), which has the highest pollution level, is 53.9%, and the removal rates of phenanthrene PHE (initial concentration 44.2 mg / kg), anthracene ANT (initial concentration 11.9 mg / kg) and fluoranthene FLT (initial concentration 98.6 mg / kg) are 73.2%, 55.3% and 58.7%, respectively. These results show that CM@ZVI has a relatively good remediation effect on 3- and 4-ring PAHs and has certain application prospects in treating actual contaminated soil. If the conditions are further optimized, the removal rate is expected to be better.
[0071] The present invention provides a weathered coal-loaded zero-valent iron composite material and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a weathered coal-loaded zero-valent iron composite material, characterized in that: The steps include: (1) Grind the weathered coal, remove impurities, and store it in a brown storage bottle and seal it; (2) adding the weathered coal obtained in step (1) into an aqueous solution of potassium ferrate, stirring and mixing at room temperature, drying and grinding, and then calcining at high temperature under an inert atmosphere; (3) The calcined product in step (2) is cooled to room temperature and washed with pure water until it becomes neutral, and finally vacuum dried to obtain the product.
2. The method for preparing the weathered coal-loaded zero-valent iron composite material according to claim 1, characterized in that: In step (1), the mass fraction of humic acid in the weathered coal is above 30%, and the inorganic component contains aluminosilicate.
3. The method for preparing the weathered coal-loaded zero-valent iron composite material according to claim 1, characterized in that: In step (1), the weathered coal is first dried at 60-80°C for 6-12 hours, ground through a 100-200 mesh sieve, washed and filtered to remove water-soluble impurities, then dried and ground again to obtain weathered coal fine powder with an average particle size of no more than 30 microns.
4. The method for preparing the weathered coal-loaded zero-valent iron composite material according to claim 1, characterized in that: In step (2), the mass concentration of potassium ferrate in the potassium ferrate aqueous solution is 0.1-1 g / 50 ml; and the mass ratio of the weathered coal to potassium ferrate is (10:1)-(1:1).
5. The method for preparing the weathered coal-loaded zero-valent iron composite material according to claim 1, characterized in that: In step (2), the stirring and mixing is magnetic stirring and mixing, the stirring speed is 500-600 r / min, and the stirring time is 10-12 h; the drying is carried out at 60-80° C. for 12-24 h; and the grinding is carried out using an agate mortar.
6. The method for preparing the weathered coal-loaded zero-valent iron composite material according to claim 1, characterized in that: In step (2), the high temperature calcination is carried out under the following conditions: heating to 600-900°C at a heating rate of 5-10°C / min, and then calcining for 1-3h.
7. The method for preparing the weathered coal-loaded zero-valent iron composite material according to claim 1, characterized in that: In step (3), the neutral pH is 7-7.5; the vacuum drying is carried out at 60°C-80°C for 12h-24h, and then sealed and stored to isolate from air.
8. The weathered coal-loaded zero-valent iron composite material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the weathered coal-loaded zero-valent iron composite material according to claim 8 in activating permonosulfate to adsorb and degrade polycyclic aromatic hydrocarbons in water or soil.
10. The use according to claim 9, characterized in that: The polycyclic aromatic hydrocarbons are at least one of naphthalene, phenanthrene and pyrene.
Citation Information
Patent Citations
Long-term stable biochar-zero-valent iron composite material and one-step preparation method thereof
CN111569831A
Nitrogen-doped fulvic acid-based porous carbon material as well as preparation method and application thereof
CN114260000A
Preparation method of lignite-based magnetic activated carbon and wastewater treatment method
CN114768765A
HUMIC SILANOL DERIVATIVES, METHOD OF THEIR PRODUCTION AND APPLICATION
RU2012150081A